Analysis of the implementation of the independent curriculum at Negeri 2 Sumobito - Mey Mayangsari (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
This research aims to determine the preparation, implementation and obstacles in implementing the independent curriculum at SMP Negeri 2 Sumobito. The method used in this research is descriptive qualitative. The data collection techniques used were interviews, observation and documentation. The research results show that independent curriculum planning is carried out based on the independent teaching platform. The implementation of the independent curriculum at SMP Negeri 2 Sumobito, which is also a driving school, has been carried out well, this is proven by the ability to implement the independent curriculum for the 2nd level of the independent change category. Although in its implementation there are still many obstacles that need to be corrected, such as low levels of literacy and numeracy, there are still empty hours and less than optimal use of PMM. However, these obstacles can also be minimized by coaching school principals, school supervisor workshops, maximizing teacher picketing, carrying out FGDs, IHT (In House Training) by colleagues or school principals regarding the use of PMM. The key to successful implementation of the independent curriculum at SMP Negeri 2 Sumobito is the principal and educators who have the will to make changes. The school principal as the leader, apart from coordinating, also continues to optimize the human resources in the school so that they are willing to make more advanced mindset changes in order to achieve an increasingly optimal implementation of the independent curriculum.